Еstablishment of types of the constitutions in students-athletes and in students-medicists with their further analysis - Karatieieva, Svitlana; Slobodian, Oleksandr; Honchar, Halyna; Nazarevych, Volodymyr; Slobodian, Kseniya; Королянчук, Андрій (My University, 2022)
Objective: The aim: Establishing anthropometric parameters and determining the patterns of formation of types of constitution in students-athletes and medical students while studying in higher education. Patients and methods: Materials and methods: We conducted a study of anthropometric parameters on 129 first and second year students of higher educational institutions in Chernivtsi (aged 16 to 21). The vast majority of students - 121 (93.8%), were from 17 to 19 years, 16 years - 5 (3.9%), 21 years - 2 (1.5%), 21 years - 1 student (0.8 %). Of these, 83 (64.4%) were male and 46 (35.6%) were female. All respondents are divided into two groups: the main group - 89 (69%), control group - 40 (31%). Among the students of the main group there were 62 (69.7%) male and 27 (30.3%) female. The control group consists of 21 (52.5%) men and 19 (47.5%) women. Students of the main group, in addition to physical activity, which was included in the program of their specialty, additionally engaged in the following sports: football - 40 (44.9%) students, volleyball - 18 (20.3%), tennis - 10 (11.2 %), fitness - 9 (10.1%), basketball - 7 (7.9%), freestyle wrestling - 5 (5.6%).All students underwent anthropometric research, according to the method of VV Bunak in the modification by PP Shaparenko. Anthropometric survey included the definition of total (length and body weight) and partial dimensions - longitudinal, transverse, circumferential. Determination of the somatotype was performed by MV Chornorutsky based on the Pinier index L - (P + T), L - body length, P - weight, T - chest circumference. In hypostenics (asthenics) this index is more than 10, in hypersthenics less than 10, in normosthenics in the range from 10 to 30 and according to V.M. Shevkunenko, where Ind: length of the lower limb / height x 100. Based on the index, dolichomorphic type of structure of the lower limb corresponds to a value greater than 55, from 50 to 55 indicates a mesomorphic (middle) type of structure of the lower limb. If the figure is less than 50 - brachymorphic type of structure. Results: Results: The probable difference of types of the constitution of students of the main group for MV Chornorutsky on the based the Pinier index and VM Shevkunenko, using the Shevkunenko index. So, between the asthenic type and the hypersthenic type of constitution, because in the main group, according to the Pinier index of asthenics - 26 (29.2%), while according to the Shevkunenko index - 3 (3.4%). Hypertensives according to the Pinier index are - 9 (10.1%), on the difference according to the Shevkunenko index - 25 (28%). The result of a study of students in the control group based on the Pinier index by MV Chornorutsky, and according to VM using the Shevkunenko index, Shevkunenko also showed a significant difference for all types of constitution: according to the Pinier index of normosthenics - 23 (57.5%), while according to the Shevkunenko index - 19 (47,%), according to the Pinier index - 7 (17.5%) - hypertensive, according to the Shevkunenko index - 25 (28%), according to MV Chornorutsky, asthenics - 10 (25%) at the same time as according to Shevkunenko dolichomorphic type of constitution in students of the control group, was not observed during the study. Conclusion: Conclusions: There is a significant discrepancy in terms of determining the types of constitution, according to MV Chornorutsky, based on the Pinier index and VM Shevkunenko, using the Shevkunenko index. Based on this, it is necessary to further study this issue because the criteria and methods of evaluation, indices, analysis of index results and in order to find common approaches to the methodology of establishing the types of constitution remain unrelated.
Keywords: Аnthropometry; Students; Type of the constitution